2007
DOI: 10.1534/genetics.107.077859
|View full text |Cite
|
Sign up to set email alerts
|

Complex Genetic Changes in Strains of Saccharomyces cerevisiae Derived by Selection in the Laboratory

Abstract: Selection of model organisms in the laboratory has the potential to generate useful substrates for testing evolutionary theories. These studies generally employ relatively long-term selections with weak selective pressures to allow the accumulation of multiple adaptations. In contrast to this approach, we analyzed two strains of Saccharomyces cerevisiae that were selected for resistance to multiple stress challenges by a rapid selection scheme to test whether the variation between rapidly selected strains migh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2008
2008
2011
2011

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…Newer methods, such as gene prospecting [ 3 ], have been developed that are higher throughput, however such methods are still limited by the fact that many favorable phenotypes, like sustained thermotolerance, often require genome-wide changes [ 4 ] that are difficult to select for by inserting individual genes or even groups of genes. The only practical way to alter such complex phenotypes is using continuous culture to select for genetic variants that can adapt to gradual changes in environmental conditions – in essence, harnessing the power of evolution by natural selection [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Newer methods, such as gene prospecting [ 3 ], have been developed that are higher throughput, however such methods are still limited by the fact that many favorable phenotypes, like sustained thermotolerance, often require genome-wide changes [ 4 ] that are difficult to select for by inserting individual genes or even groups of genes. The only practical way to alter such complex phenotypes is using continuous culture to select for genetic variants that can adapt to gradual changes in environmental conditions – in essence, harnessing the power of evolution by natural selection [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Two investigations reported that oxidative stress resistance is a quantitative trait in S. cerevisiae (Perlstein et al 2006;Witten et al 2007). Witten et al (2007) evolved two yeast strains for oxidative stress resistance and showed that both strains acquired the same unknown major-effect mutation but differed in the nature of unidentified segregating modifiers.…”
mentioning
confidence: 99%
“…Witten et al (2007) evolved two yeast strains for oxidative stress resistance and showed that both strains acquired the same unknown major-effect mutation but differed in the nature of unidentified segregating modifiers. Perlstein et al (2006) tested growth inhibition in F 1 segregants in response to small molecules, including H 2 O 2 , and came to the conclusion that two as of yet undiscovered loci affect oxidative stress resistance.…”
mentioning
confidence: 99%